Analisis Pembelajaran Pendidikan Jasmani Olahraga dan Kesehatan (PJOK) di Masa Pandemi Covid-19 Kelas 2 di SDN Cibodas 2 Tangerang - Elina Elina; Samsul Azhar; Syaeful Bahri (Jurnal Halaqah, 2021)
Research This study aims to find out and analyze the Learning of Physical Education in Sports and Health (PJOK) During the Covid-19 Pandemic Period 2 at SDN Cibodas 2 Tangerang. The method used in this research is a qualitative method, which is to examine and analyze the data objectively according to the data collected in the field. Then the data collected from the research results are described in the form of words. The data analysis was done through observation, documentation, and interviews. In this study, 1 PJOK teacher and 14 students as subjects. The results of this study indicate that teachers continue to provide PJOK learning, teachers use online/distance learning methods, so that the learning process continues to run smoothly by using WhatsApp group learning media to make it easier for teachers to convey material, especially in PJOK learning, . It can be seen from the results of the practice that they send via videos in the whatsapp group that most of them are able to practice the material presented correctly and students can be more creative.